AFRP20: New P‐Wavespeed Model for the African Mantle Reveals Two Whole‐Mantle Plumes Below East Africa and Neoproterozoic Modification of the Tanzania Craton - A. Boyce; I. D. Bastow; S. Cottaar; R. Kounoudis; J. Guilloud De Courbeville; E. Caunt; S. Desai (Geochemistry, Geophysics, Geosystems, 2021)
Abstract Africa's Cenozoic tectonism is often attributed to mantle plumes, particularly below East Africa, but their morphology, number, location, and impact on the African lithosphere are debated. The broad slow wavespeed African Superplume, ubiquitous in large‐scale tomographic models, originates below South Africa, reaching the surface somewhere below East Africa. However, whether the diverse East African mantle geochemistry is best reconciled with one heterogeneous upwelling, or current tomographic models lack the resolution to image multiple distinct plumes, remains enigmatic. S‐wavespeed tomographic images of Africa are legion, but higher frequency P‐wavespeed whole‐mantle models possessing complementary diagnostic capabilities are comparatively lacking. This hinders attempts to disentangle the effects of Cenozoic hotspot tectonism and Pan African (and older) tectonic events on the East African lithosphere. Here we develop a continental‐scale P‐wave tomographic model capable of resolving structure from upper‐to‐lower mantle depths using a recently developed technique to extract absolute arrival‐times from noisy, temporary African seismograph deployments. Shallow‐mantle wavespeeds are δVP ≈ −4% below Ethiopia, but less anomalous (δVP ≥–2%) below other volcanic provinces. The heterogeneous African Superplume reaches the upper mantle below the Kenyan plateau. Below Ethiopia/Afar we image a second sub‐vertical slow wavespeed anomaly rooted near the core‐mantle boundary outside the African LLVP, meaning multiple disparately sourced whole‐mantle plumes may influence East African magmatism. In contrast to other African cratons, wavespeeds below Tanzania are only fast to 90–135 km depth. When interpreted alongside Lower Eocene on‐craton kimberlites, our results support pervasive metasomatic lithospheric modification caused by subduction during the Neoproterozoic Pan‐African orogeny.